A discourse analysis of 1 John - Rand, J. A. du (Neotestamentica, 1979)
We know that we possess the eternal life and we are obliged to illustrate this fact in our way of living. The source of this certainly rests upon the incarnation of Jesus Christ and the realization of this certainly lies in fellowship, filiation and love.
free
Keywords: Eternal life; Fellowship; filiation and love; Incarnation of Jesus Christ